Developing Ozone Risk Assessment for Larch Species - Hoshika, Yasutomo; Paoletti, Elena; Agathokleous, Evgenios; Sugai, Tetsuto; Koike, Takayoshi (Frontiers in Forests and Global Change, 2020)
Ozone (O3) risk assessment for the protection of forests requires species-specific critical levels (CLs), based on either O3 concentrations (AOT40) or stomatal uptake (PODY) accumulation over the growing season. Larch (Larix sp.) is a genus with O3-susceptible species, widely distributed in the northern hemisphere and with global economic importance. We analyzed published and unpublished data of Japanese larch (L. kaempferi) and its hybrid F1 (L. gmelinii var. japonica × L. kaempferi) responses to O3 exposure for developing a parameterization of stomatal conductance model and estimating PODY-based CLs with two Y thresholds, i.e. 0 and 1 nmol m-2 s-1 PLA. In parallel, we estimated AOT40-based CLs. The results show that the AOT40-based CLs for a 2% and 4% biomass loss in Japanese larch were 5.79 and 11.59 ppm h, i.e. higher than in hybrid larch F1 (2.18 and 4.36 ppm h AOT40), suggesting a higher O3-susceptibility of the hybrid. However, the use of PODY reconciled the species-specific differences, because the CLs were similar; i.e. 9.40 and 12.00 mmol m-2 POD0 and 2.21 and 4.31 mmol m-2 POD1 in Japanese larch, vs. 10.44 and 12.38 mmol m-2 POD0 and 2.45 and 4.19 mmol m-2 POD1 in the hybrid, for 2% and 4% biomass loss, respectively. Overall, the CLs were lower than in other forest species, which suggests a relatively high susceptibility of these larches. These results will inform environmental policy-makers and modelers about larch susceptibility to O3.